The impact of administrative empowerment on employee performance: A field study in pharmaceutical companies listed on Amman stock exchange - Alqudah, Enas Hani (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to investigate the effect of managerial empowerment with its dimensions (authority delegation, autonomy, motivation) on the performance of employees in the pharmaceutical industry companies at Amman Stock Exchange from the view of managers and employees on these companies. The study assumed that there is no a significant relationship between the dimensions of managerial empowerment and the performance of employees at a level of statistical significance (α
Keywords: administrative empowerment; employee performance; pharmaceutical companies listed on the Amman Stock Exchange